Nile crocodile (Crocodylus niloticus) genetic diversity and population structure, within the lower Kunene and Okavango Rivers of northern Namibia - Versfeld, William F. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.